Sustainable and Healthy Territories in the SUS: the intrinsic relationship with the Agenda 2030 - Gadelha, Paulo (2024)
This article highlights the vital importance of integrating the Sustainable Development Goals of the 2030 Agenda within the scope of the Brazilian Unified Health System, emphasizing the need for community action and cooperation to promote sustainable development and health. Territorialization, combined with social technologies, is crucial, as evidenced by initiatives from Oswaldo Cruz Foundation, highlighting the essentiality of this approach for an equitable and sustainable future.